Civil liability for representatives of pharmaceutical companies comparative study - Assistant Prof. Dr. Nizar Hazim Mohammed Al-Damalooji (The college of law and political science journal, 2025)
The issue of drug production and circulation has an important place in legal legislation because medicine is considered one of the necessary commodities that are linked to public health and national security. From this standpoint, most countries have sought to establish what is called drug security by following pharmaceutical policies in order to provide safe medicine for their citizens. Perhaps providing medicines alone is not enough to achieve the desired goal. Methods must be found to distribute and promote medicines and the danger that accompanies that, especially if this role is played by people who are not specialists or who do not have scientific and technical knowledge in this subject. The responsibility of this group goes beyond just being intermediaries in the sales process, but rather because they represent the last link for the drug to reach the consumer, and therefore they are in a position where they must have the experience and technical and scientific know-how to ensure the safety of the product before distributing it. Any defect in these products leads to serious consequences for the health of the individual and society. In order to achieve the responsibility of this group of professionals, the well-known elements of responsibility must be present, which are represented by the error of the representative distributing the drug, such as not ensuring the safety of the product he is distributing, the harm caused to the customer or the consumer, and the causal relationship between the harm caused to the patient as a result of using the drug and the error of the representative distributing this. The medicine.